Syntaxic tools for creating the image of Ukraine in media space - Pliasun, Olga (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article analyzes syntactic potential of constructing the image of Ukraine in modern mass media. The author argues for the need to apply a comprehensive approach to the analysis of language tools of image construction. In particular, the scholar emphasizes the importance of exploring different types of image media texts that are the main carriers of image information about the country. The scientist’s attention is focused on the ambivalence of most image texts, which, depending on the author’s intention, subjective interpretation of the information covered can have both a positive and a negative impact on the state image. The paper consistently proves that the features of constructing the image of Ukraine are most clearly revealed at the syntactic level, which is explained by the specific intonation of the phrase, the emotional-evaluative nature of the presentation of the material, etc. The image potential of different types of oppositions, where the first component forms a positive state image and the second component contributes to the formation of a negative image of Ukraine, is analyzed. Moreover, a highly productive syntactic tool for shaping the image of the country is syncrisis based on contextual opposition. Equally effective in the process of constructing the state image is the use of expressive syntax. Thus, in particular, the use of rhetorical exclamations in image media publications with meliorative meaning contributes to the construction of a positive state image. At the same time, rhetorical questions introduced into the image text often have pejorative semantics and thus form a negative image of Ukraine. In addition, effective syntactic means of creating state image in media are anepiphor, parceling and antiphrase statements that emphasize the author’s attitude to the events described. The conducted research convinces that the syntactic system of language represents a wide palette of expression of author’s modality, subjective-evaluative interpretation of information and, as a result, the image of the state that is formed in the mass consciousness.